TUTURAN IMPERATIF PADA AYAT-AYAT MUNAKAHAT DALAM AL-QUR’AN KAJIAN PRAGMATIK - Gozali, Imron (Ekonomi Syariah STAI Sangatta Kutai Timur, 2020)
This paper discusses the imperative utterance ofMuhakahat verses in the Qur'an by using speech act theory. Imperative speech has various forms and functions according to the context. The method used is an analytic descriptive method. The author describes the exposure of the verses of Munakahat and then analyzes them with speech act theory. Systematics used; The first is an introduction, the second is a pragmatic study, the third is imperative speech or command sentences, the fourth is an analysis of the imperative speech in munakahat verses with speech act theory, and the last is a conclusion.